(1658) Business Intelligence in the Strategic Management of Egyptian Institutions الذكاء التجاري في الإدارة الاستراتيجية للمؤسسات المصرية - El Haddad, Basmah (معهد التخطيط القومى, 2022)

(untitled)
All businesses and organizations seek excellence and economic prosperity in light of the many changes surrounding and affecting the working environment. The institutional and organizational need to obtain important strategic information to make strategic decisions increased. Maximizing benefits of resources and working conditions and profit became one of their most important goals, as well as raising the advantages and competitive position. In this context, institutions and business organizations are interested in developing their plans, goals and strategic objectives to achieve the highest efficiency and effectiveness to maximize their various benefits. The research examines and explains how to integrate business intelligence models, tools and applications, architectures and structures in the business enterprises and institutions